Islr regulates canonical Wnt signaling-mediated skeletal muscle regeneration by stabilizing Dishevelled-2 and preventing autophagy. Issue 1 (December 2018) - Zhang, Kuo; Zhang, Yuying; Gu, Lijie; Lan, Miaomiao; Liu, Chuncheng; Wang, Meng; Su, Yang; Ge, Mengxu; Wang, Tongtong; Yu, Yingying; Liu, Chang; Li, Lei; et al.
Abstract Satellite cells are crucial for skeletal muscle regeneration, but the molecular mechanisms regulating satellite cells are not entirely understood. Here, we show that the immunoglobulin superfamily containing leucine-rich repeat (Islr), a newly identified marker for mesenchymal stem cells, stabilizes canonical Wnt signaling and promote skeletal muscle regeneration. Loss ofIslr delays skeletal muscle regeneration in adult mice. In the absence of Islr, myoblasts fail to develop into mature myotubes due to defective differentiation. Islr interacts with Dishevelled-2 (Dvl2) to activate canonical Wnt signaling, consequently regulating the myogenic factor myogenin (MyoG). Furthermore, Islr stabilizes Dvl2 by reducing the level of LC3-labeled Dvl2 and preventing cells from undergoing autophagy. Together, our findings identify Islr as an important regulator for skeletal muscle regeneration. "Satellite cells are crucial for skeletal muscle regeneration. Here the authors show that immunoglobulin superfamily containing leucine-rich repeat (Islr) promotes skeletal muscle regeneration via a mechanism involving Dishevelled-2 stabilization in satellite cells and protection from autophagy.